Molecular Detection of VEB and OXA-23 Resistance Gene in Pseudomonas Aeruginosa Isolates at Dr. Wahidin Sudirohusodo Hospital Makassar - Andi Zsazsa Rafiatul Mukhlis; Rizalinda Sjahril; Firdaus Hamid (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Pseudomonas aeruginosa is a common gram-negative pathogen in nosocomial infections in immune-compromised patients. It exhibits high rates of intrinsic resistance to many classes of antibiotics, especially beta-lactam antibiotics. Production of extended-spectrum beta-lactamase (ESBL) and genes belonging to the carbapenem-hydrolyzing class D subgroup β-lactamases (CHDL) are a problem for increasing antibiotic resistance worldwide. This study aimed to identify P. aeruginosa containing the VEB and OXA-23 genes. Eighty-five clinical isolates of P. aeruginosa from various clinical samples were identified and tested for antimicrobial susceptibility using VITEK 2 compact. VEB and OXA-23 genes were detected using the Polymerase Chain Reaction (PCR) method. The PCR results revealed that 13 (15.3%) of P. aeruginosa isolates were positive OXA-23 gene, but no isolate positive for the VEB gene in P. aeruginosa isolates. The study results demonstrated the spread of the OXA-23 gene in P. aeruginosa isolates at Dr. Wahidin Sudirohusodo Hospital Makassar.